Rebelión en San Ignacio de Chiquitos (1790) - Martínez, Cecilia (Jahrbuch für Geschichte Lateinamerikas, 2018)
The aim of this article is to describe and explain the indigenous rebellion that took place in San Ignacio de Chiquitos (current eastern Bolivia) the 5th of June of 1790 when a group of natives burst into the priest’s house and attacked his guests. Four of them were killed and eight were seriously wounded. Furthermore, the rebels expelled the priest Simón Vera y Gallo, his nephew and other non-Indian people who lived in the town. In order to analyse this uprising, the studies on the 1780 Andean indigenous rebellions are used as methodologic and heuristic references. At the same time, the rebellion in San Ignacio is considered within the frame of the local political and social conditions trying to address the native rebels’ point of view.
Keywords: Uprising; Indians; 18th Century; Lowlands of South America